Titanium and Other Metal Hypersensitivity Diagnosed by MELISA® Test: Follow-Up Study - Vrbova, Radka; Podzimek, Stepan; Himmlova, Lucie; Roubickova, Adela; Janovska, Marketa; Janatova, Tatjana; Bartos, Martin; Vinsu, Alex (BioMed research international, 2021)
This study is aimed at proving the clinical benefit of the MELISA® test in the minimization or complete elimination of health problems in patients with confirmed hypersensitivity to metals used for tissue replacements. A group of 305 patients aged 20-75 years with previously proven metal hypersensitivity (initial MELISA® test), mainly to titanium and then to another fifteen metals, was chosen from the database at the Institute of Dental Medicine. From these patients, a final group of 42 patients agreed to participate in the study, 35 of which were female and 7 were male. The patients completed a special questionnaire aimed at information regarding change of health status from their last visit and determining whether the results of the initial MELISA® test and recommendations based on it were beneficial for patients or not. They were clinically examined, and peripheral blood samples were taken to perform follow-up MELISA® tests. Questionnaire data was processed, and the follow-up MELISA® test results were compared with the results of the initial MELISA® tests. For statistical analysis, the Fisher's exact test and paired T-test were used. Thirty-two patients reported that they followed the recommendations based on the results of the initial MELISA® tests, and of these, 30 patients (94%) confirmed significant health improvement. Six patients did not follow the recommendation, and from these, only one patient reported an improvement in his health problems. By comparison of the initial and follow-up MELISA® test results, it can be stated that the hypersensitivity to the given metal decreased or disappeared after the therapeutic interventions performed based on the initial MELISA® test results. The evaluation of the data obtained from patients in this study confirmed a significant clinical benefit of MELISA® test.
Keywords: Male; lidé středního věku; Surveys and Questionnaires; Humans; Middle Aged; senioři; mužské pohlaví; Female; Titanium; následné studie; Aged; ženské pohlaví; průzkumy a dotazníky; Follow-Up Studies; Hypersensitivity; Adult; alergie; dospělí; lidé; titan